Respuesta :

Hi,

Let's solve the equation step-by-step.

x−3x=2(4+x)

Step 1: Simplify both sides of the equation.

x−3x=2(4+x)

x+−3x=(2)(4)+(2)(x)(Distribute)

x+−3x=8+2x

(x+−3x)=2x+8(Combine Like Terms)

−2x=2x+8

−2x=2x+8

Step 2: Subtract 2x from both sides.

−2x−2x=2x+8−2x

−4x=8

Step 3: Divide both sides by -4.

−4x/−4 =  8/−4

x=−2

Answer:

x=−2

Have a great day!

X - 3X = 2(4+X)

Distributive Property:

X-3X = 8+2X

Subtraction Prperty:

-2X = 8+2X

Subtraction Property:

-4X = 8

Division Property:

x = 8/-4

X = -2